Perioperative nursing of a patient with stent-graft infection and aortoesophageal fistula after thoracic endovascular aortic repair (1例主动脉腔内修复术后支架感染并发食管瘘患者的围术期护理) - XIAO Lixiang (肖立香); SU Yunyan (苏云艳); WU Mengya (伍梦雅) (中西医结合护理)
This paper summarized the perioperative nursing management of a patient with stent-graft infection and aortoesophageal fistula after thoracic endovascular aortic repair (TEVAR). Nurses had enhanced the prevention of stent-graft infection and evaluated the influence of stent implantation on trachea and esophagus before surgery. Key issues of postoperative nursing included maintaining effective circulating volume, esophageal repair management, nutrition support, functional rehabilitation exercise, psycho-social support. (本文总结1例主动脉腔内修复术后支架感染并发主动脉食管瘘患者的围术期护理经验和体会。护理要点包括: 术前加强移植物感染的护理, 评估支架对周围气管食管的影响; 术后维持有效循环, 完善食管修补术后护理、营养支持、功能锻炼康复护理、心理社会支持等。)